Transformation into a research university: conceptual model and milestonest - Hüseynov, Həsən (Institute of Education of the Republic of Azerbaijan, 2026)
The creation of research universities in a knowledge economy and under conditions of global scientific and technological competition is one of the main tools for increasing national innovation potential and international academic competitiveness. The purpose of this article is to develop a systematic conceptual model for transforming an existing traditional university into a research university. For the transformation process, a model is proposed that includes stages such as strategic management, research infrastructure, personnel policy, educational programs, financing, and international integration. The obtained results can be used in the development of university development programs and modernization strategies.
Keywords: Knowledge economy; Conceptual model; High-tech equipment; Research university